PENANAMAN NILAI-NILAI AGAMA PADA ANAK USIA DINI MELALUI PEMBIASAAN KEGIATAN KEAGAMAAN DI RA AL-MAA’UUN KECICANG ISLAM KARANGASEM BALI - Ilzam Dhaifi; Mudrika Mudrika (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2021)
This study was intended to determine the inculcation of religious values ​​in early childhood through the habituation of religious activities in RA Al-Maa'unun Kecicang Islam Karangasem Bali. This research is included in qualitative research, so the problem is discussed through field studies conducted at RA Al-Maa'uun Kecicang Islam. Data obtained from several sources by means of observation, unstructured interviews, and documentation. From all the data that has been obtained then processed with descriptive analysis. This research has found that the inculcation of religious values ​​in early childhood in RA Al-Maa'uun is carried out every day and the learning is more devoted on Friday. In every activity RA Al-Maa'uun tries to include religious values ​​in each of the activities carried out, for example accustoming students to recite prayers before and after doing activities. The results of the inculcation of religious values ​​can be seen from the attitude of students and students who have begun to change for the better, the awareness of parents who initially paid less attention to the development of children's religion now become more motivated to always pay attention to the development of children's religion, as well as the RA Al-Maa'uun institution have the trust of students' parents and the community that RA Al-Maa'uun is able to produce a generation of qualified Muslims and Muslims.